Hepatocyte Growth Factor/C-Met Axis in Thyroid Cancer: From Diagnostic Biomarker to Therapeutic Target. Issue 12 (24th March 2017) - Trovato, Maria; Campennì, Alfredo; Giovinazzo, Salvatore; Siracusa, Massimiliano; Ruggeri, Rosaria Maddalena
The hepatocyte growth factor (HGF)/c-met axis plays a crucial role in cancer development by promoting cellular proliferation, motility, and morphogenesis, as well as angiogenesis. Different cellular distributions of both the ligand and the receptor in benign vs malignant lesions indicate this biological system as a candidate for a diagnostic biomarker of malignancy occurring in endocrine glands, such as the thyroid and pituitary. Furthermore, the HGF/c-met expression may help to identify a subset of patients eligible for potential targeted therapies with HGF/c-met inhibitors or antagonists in thyroid tumour, as well as in other malignancies. This may be relevant for iodine-refractory cancers, the treatment of which is still a major challenge. With this in mind, HGF/c-met expression in thyroid cancer tissue may be useful for prognostic and therapeutic stratification of patients.